Hubungan Pola Komunikasi Guru dengan Pembelajaran Siswa Berkebutuhan Khusus - M. Rafif Kamil; Tresna Wiwitan (UNISBA Press, 2024)
Abstract. Inclusion schools are educational institutions that aim to provide education for all students, including children with special needs or disabilities. The main idea behind inclusive schools is to provide equal rights to all students without discrimination based on differences in abilities, needs and personal characteristics. A teacher must have a communication pattern that is used during learning activities, to convey messages that are easily accepted by all students, including students with special needs in inclusive schools. So this is what made the author conduct research with the title